Electronic Customer Relationship Management (E-CRM) - Sudhakar, V. (Indian Journal of Marketing, 2009)
CRM is the seamless co-ordination between sales, customer service, marketing field support and other customer-touching functions. It integrates people, processes and technology to maximize relationship with all customers and partners, e-customers, distributional channel numbers, internal customers and suppliers. CRM results in a number of benefits to an organization like increased margins improve customer satisfaction ratings and decrease administrative costs. The phenomenon of building a relationship with customers via the internet is known as electronic CRM (e-CRM). The objective of the CRM and e-CRM are the same- the difference is the medium used for providing services to the customer. E-CRM focuses on electronic channels mainly on the internet and on technologies that enable automated and electronic management of customer relations. E-CRM is a multi-faceted strategy that helps companies understand, anticipate and manage customer needs. A major thrust of it involves segmenting customers and offering appropriate and differentiated services for each of these levels. It mainly uses the electronic media to integrate and simplify customer-related business processes, drastically reducing costs of customer-facing operations while achieving CRM’s primary goal to enhance the customer experience.